2011
DOI: 10.1021/mp200088z
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Dependence of 5-Aminosalicylic Acid Pharmacological Actions in Intestinal Mucosa after Oral Administration of a pH-Dependent Formulation

Abstract: Asacol, a medication that delivers delayed release 5-aminosalicylic acid (5-ASA), is a useful therapeutic agent for inflammatory bowel disease (IBD), but the relationship between its pharmacological actions and intestinal concentrations has not been studied in detail. Therefore, our aim was to assess 5-ASA's pharmacological actions as a function of its concentration at its target site. We first evaluated 5-ASA's release profiles in vitro by the paddle method and found that Asacol starts to release 5-ASA at pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…As a result, it is important to achieve a high 5-ASA concentration in mucous membranes to maintain remission of UC. [2][3][4][5] When administered as an oral time-dependent release formulation, half of it is absorbed in the small intestine. This reduces the efficacy of 5-ASA for treating UC since the major lesions are found in the large intestine, unlike Crohn's disease, which mainly affects the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is important to achieve a high 5-ASA concentration in mucous membranes to maintain remission of UC. [2][3][4][5] When administered as an oral time-dependent release formulation, half of it is absorbed in the small intestine. This reduces the efficacy of 5-ASA for treating UC since the major lesions are found in the large intestine, unlike Crohn's disease, which mainly affects the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the amount of 5-ASA in the intestinal mucosa above the threshold concentrations required to affect target molecules involved in inflammation can be regarded as a surrogate marker of therapeutic effects (33). By performing experiments with dogs, it was confirmed that sufficiently high concentrations of 5-ASA in the colonic mucosa can be achieved by oral administration of pH-dependent release formulation Asacol ® , with only low amounts detected in tissue of the small intestine (34). In contrast, the time-controlled release from Pentasa ® resulted in a considerable 5-ASA plasma concentration several hours after administration, confirming the advantage of galenic protection in the upper small intestine as higher plasma concentrations are associated with an increased risk of systemic side effects.…”
Section: Measurement Of Drug Release In Healthy Individuals and Patientsmentioning
confidence: 96%
“…This polymer has pH-sensitive solubility: it does not dissolve at the pH of the stomach or proximal small intestine, and only dissolves at a pH higher than 7 in the distal small intestine to release drugs in a colon-specific manner . After Asacol administration to dogs, drug concentration was about 10 times higher in the colonic mucosa than the small intestine, and higher than the inhibitory concentration 50 (IC 50 ) for suppression of inflammatory processes . Compared with Pentasa sustained release tablet, consisting of EC-coated microgranules of mesalamine, and Salazopyrin EN-tabs, a mesalamine prodrug, a clinical study also showed high drug concentrations in the sigmoid colon mucosa after dosing Asacol to patients .…”
Section: Site- and Amount-controlled Ddsmentioning
confidence: 99%
“…163 After Asacol administration to dogs, drug concentration was about 10 times higher in the colonic mucosa than the small intestine, and higher than the inhibitory concentration 50 (IC 50 ) for suppression of inflammatory processes. 164 Compared with Pentasa sustained release tablet, consisting of EC-coated microgranules of mesalamine, and Salazopyrin EN-tabs, a mesalamine prodrug, a clinical study also showed high drug concentrations in the sigmoid colon mucosa after dosing Asacol to patients. 165 In another clinical study, significant efficacy was observed with Asacol, but not with Pentasa, in proctitis-type UC patients, albeit that overall assessment of the two types of formulation was similar.…”
Section: Site-and Amount-controlled Ddsmentioning
confidence: 99%